2007
DOI: 10.1021/ol063027h
|View full text |Cite
|
Sign up to set email alerts
|

N-Vinylpyridinium and -ammonium Tetrafluoroborate Salts: New Electrophilic Coupling Partners for Pd(0)-Catalyzed Suzuki Cross-Coupling Reactions

Abstract: N-Vinylpyridinium and -trialkylammonium tetrafluoroborate salts represent a new class of electrophilic coupling partner for Pd(0)-catalyzed Suzuki cross-coupling reactions and give very good to excellent yields of products with a wide range of boronic acids. The salts are easily prepared from activated acetylenes and pyridinium or trialkylammonium tetrafluoroborates to form crystalline, air-stable, and nonhygroscopic crystals.The Suzuki reaction is a powerful member of the important and versatile suite of pall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Buszek et al first reported an interesting example of Suzuki–Miyaura coupling for the synthesis of chalcones from N -vinylpyridinium tetrafluoroborate salt with yields of 60–81% (Scheme 4). 126 These salts represent a novel class of palladium-catalyzed electrophilic coupling partners reacting with a wide range of boronic acids. Additionally, the salts are air-stable and nonhygroscopic crystals that can be easily prepared quantitatively in one step from the activated acetylenes and either pyridinium or trialkylammonium tetrafluoroborates.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Buszek et al first reported an interesting example of Suzuki–Miyaura coupling for the synthesis of chalcones from N -vinylpyridinium tetrafluoroborate salt with yields of 60–81% (Scheme 4). 126 These salts represent a novel class of palladium-catalyzed electrophilic coupling partners reacting with a wide range of boronic acids. Additionally, the salts are air-stable and nonhygroscopic crystals that can be easily prepared quantitatively in one step from the activated acetylenes and either pyridinium or trialkylammonium tetrafluoroborates.…”
Section: Synthesismentioning
confidence: 99%
“…126 As shown in Scheme 8A, Al-Al-Masum and coworkers developed a direct cross-coupling reaction of benzoyl chlorides and potassium styryltrifluoroborates to obtain the corresponding chalcones in the presence of PdCl 2 (d t bpf) as the catalyst and K 2 CO 3 , taking advantage of microwave irradiation. Eight chalcones were synthesized using this condition, providing good to excellent yields (56–96%).…”
Section: Synthesismentioning
confidence: 99%
“…[28] Forexample, N-vinylpyridinium salts have been successfully utilized as electrophilic coupling partner in the palladium-catalyzed Suzuki reaction but necessitate increased temperatures, most likely because of an energetically unfavorable oxidative addition. [29] Theu se of unactivated alkyl amines in crosscoupling reactions had not been realized until more recently.…”
Section: N-carbon-substituted Pyridinium Reagentsmentioning
confidence: 99%
“…Buszek and Brown described N-vinylpyridinium and ammonium tetrafluoroborate salts as a new class of electrophilic coupling partners for the Suzuki-Miyaura cross-coupling reaction (Scheme 15.16) [68]. Good to excellent yields of various 3-aryl-substituted enones were obtained by treating the salts with arylboronic acids, Pd 2 (dba) 3 (5 mol%), and PCy 3 (12 mol%) under microwave irradiation.…”
Section: Cross-coupling Reactions 615mentioning
confidence: 99%